Comments on Alexia Yates’ Selling Paris: Property and Commercial Culture in the Fin-de-siècle Capital - Neumann, Tracy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
This comment is part of a roundtable on Alexia Yates’ book, Selling Paris: Property and Commercial Culture in the Fin-de-siècle Capital (Harvard University Press, 2015). In it, the author summarizes Yates’ argument, discusses her source base, and explains why historians whose interests lie beyond 19th century France should read the book.